The voltage-gated Ca2+ channel subunit α2δ-4 regulates locomotor behavior and sensorimotor gating in mice. - Annette Klomp; Ryotaro Omichi; Yoichiro Iwasa; Richard J Smith; Yuriy M Usachev; Andrew F Russo; Nandakumar S Narayanan; Amy Lee (PLoS ONE, 2022)
Voltage-gated Ca2+ channels are critical for the development and mature function of the nervous system. Variants in the CACNA2D4 gene encoding the α2δ-4 auxiliary subunit of these channels are associated with neuropsychiatric and neurodevelopmental disorders. α2δ-4 is prominently expressed in the retina and is crucial for vision, but extra-retinal functions of α2δ-4 have not been investigated. Here, we sought to fill this gap by analyzing the behavioral phenotypes of α2δ-4 knockout (KO) mice. α2δ-4 KO mice (both males and females) exhibited significant impairments in prepulse inhibition that were unlikely to result from the modestly elevated auditory brainstem response thresholds. Whereas α2δ-4 KO mice of both sexes were hyperactive in various assays, only females showed impaired motor coordination in the rotarod assay. α2δ-4 KO mice exhibited anxiolytic and anti-depressive behaviors in the elevated plus maze and tail suspension tests, respectively. Our results reveal an unexpected role for α2δ-4 in sensorimotor gating and motor function and identify α2δ-4 KO mice as a novel model for studying the pathophysiology associated with CACNA2D4 variants.